Dark Energy Survey Year 1 Results: redshift distributions of the weak-lensing source galaxies. Issue 1 (18th April 2018) - Hoyle, B; Gruen, D; Bernstein, G M; Rau, M M; De Vicente, J; Hartley, W G; Gaztanaga, E; DeRose, J; Troxel, M A; Davis, C; Alarcon, A; MacCrann, N; et al.
ABSTRACT: We describe the derivation and validation of redshift distribution estimates and their uncertainties for the populations of galaxies used as weak-lensing sources in the Dark Energy Survey (DES) Year 1 cosmological analyses. The Bayesian Photometric Redshift (bpz ) code is used to assign galaxies to four redshift bins between z ≈ 0.2 and ≈1.3, and to produce initial estimates of the lensing-weighted redshift distributions $n^i_{\rm PZ}(z)\propto \mathrm{d}n^i/\mathrm{d}z$ for members of bin i . Accurate determination of cosmological parameters depends critically on knowledge of n i, but is insensitive to bin assignments or redshift errors for individual galaxies. The cosmological analyses allow for shifts $n^i(z)=n^i_{\rm PZ}(z-\Delta z^i)$ to correct the mean redshift of n i ( z ) for biases in $n^i_{\rm PZ}$ . The Δ z i are constrained by comparison of independently estimated 30-band photometric redshifts of galaxies in the Cosmic Evolution Survey (COSMOS) field to bpz estimates made from the DES griz fluxes, for a sample matched in fluxes, pre-seeing size, and lensing weight to the DES weak-lensing sources. In companion papers, the Δ z i of the three lowest redshift bins are further constrained by the angular clustering of the source galaxies around red galaxies with secure photometric redshifts at 0.15 <  z  < 0.9. This paper details the bpz and COSMOS procedures, and demonstrates that the cosmological inference is insensitive to details of the n i ( z ) beyond the choice of Δ z i . The clustering and COSMOS validation methods produce consistent estimates of Δ z i in the bins where both can be applied, with combined uncertainties of $\sigma_{\Delta z^i}=0.015, 0.013, 0.011, $ and 0.022 in the four bins. Repeating the photo- z procedure instead using the Directional Neighbourhood Fitting algorithm, or using the n i ( z ) estimated from the matched sample in COSMOS, yields no discernible difference in cosmological inferences.